ANALISA PERBANDINGAN PENGAKUAN PAJAK PERALIHAN HAK ATAS TANAH DAN BANGUNAN PADA LAPORAN KEUANGAN KOMERSIL DAN FIKAL PADA LAPORAN PT.PRIMA KARYA ASIH - Jenni Mariana Sinaga; Ari Sunardi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
The purpose of this study is to find out how the recognition of the transfer tax on land and buildings to both commercial and financial statements for tax purposes (fiscal), where commercial financial statements are prepared based on Accounting Standards (SAK), ETAP Accounting Standards, and Accounting Standards Syariah and UMKM Accounting Standards elements of financial statements consisting of balance sheets, income statements, and capital changes and financial statement records, while in preparing financial (fiscal) financial statements, they are prepared based on applicable taxation rules in set in the Taxation Law so that differences will arise, which differences will be carried out reconciliation of commercial and fiscal financial statements to get a real report in meeting tax obligations. Based on research conducted at PT. PRIMA KARYA ASIH, the results can be described how the recognition of the transfer tax on land and buildings that are final so that income and costs related to final income are no longer accounted for in reporting in profit/loss in fiscal records